Age of First Marriage with Education and Working Status of Women at East Nusa Tenggara, Aceh, South Sulawesi, and Central Kalimantan Provinces - Cahyono, Bambang Eko (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2023)
Age at First Marriage is an important factor in family life because giving birth at a young age will affect the conditions of the child's birth and the risk of giving birth to the mother. Age at First Marriage is one of the targets and an indicator of the achievement of the national BKKBN program. The purpose of this analysis is to see the relationship between the characteristics (especially socio-economic) of women of childbearing age (WUS) aged 15–49 years and the age at first marriage in regions where the total fertility rate is still relatively high, including the provinces of NTT, Aceh, South Sulawesi, and Central Kalimantan, which is related to the achievement of the Main Performance Indicator target, namely the median age at first marriage. This research is a secondary data analysis of the 2022 Family Data Collection data. Univariate analysis is to see a picture of the socio-economic variables that have been determined; bivariate analysis is carried out to see the relationship between socio-economic factors (education and employment status) and age at first marriage. The results of the analysis show that there is a relationship between the age of first marriage and the level of education; the higher the level of education, women of childbearing age tend to marry for the first time at the age of >= 21 years. This happens in the provinces of NTT, Aceh, South Sulawesi, and Central Kalimantan. Likewise, working status has the same pattern as education level. For women aged 15–49 who are working, the age at first marriage tends to be >= 21 years. Of course, there are other factors that influence the decision not to marry for the first time at a young age, apart from these two variables. At least this description of characteristics could be a wrong consideration when carrying out program interventions in an effort to increase the age at first marriage, especially for women of childbearing age who are still unmarried.